2022
DOI: 10.3389/fphys.2022.1037750
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of (smoking-related) non-communicable diseases—Evidence for a common underlying pathophysiological pattern

Abstract: Non-communicable diseases, like diabetes, cardiovascular diseases, cancer, stroke, chronic obstructive pulmonary disease, osteoporosis, arthritis, Alzheimer’s disease and other more are a leading cause of death in almost all countries. Lifestyle factors, especially poor diet and tobacco consumption, are considered to be the most important influencing factors in the development of these diseases. The Western diet has been shown to cause a significant distortion of normal physiology, characterized by dysregulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 248 publications
0
8
0
Order By: Relevance
“…It is acknowledged that lifetime smoking rates are higher in patients who are diagnosed with major depression disorder (59%), bipolar disorder (83%), or schizophrenia and other mental disorders (90%), compared to 32% among adults with no mental illness [ 25 ]. Studies have indicated that exposure to cigarette smoke and/or nicotine, through active and passive smoking, causes a complex dysregulation of the sympathetic nervous system and immune system, as well as disruption of physiological oxidant/antioxidant homeostasis, all of which play a key role in the aggravation of a broad spectrum of diseases, including mental disorders [ 12 , 13 , 16 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is acknowledged that lifetime smoking rates are higher in patients who are diagnosed with major depression disorder (59%), bipolar disorder (83%), or schizophrenia and other mental disorders (90%), compared to 32% among adults with no mental illness [ 25 ]. Studies have indicated that exposure to cigarette smoke and/or nicotine, through active and passive smoking, causes a complex dysregulation of the sympathetic nervous system and immune system, as well as disruption of physiological oxidant/antioxidant homeostasis, all of which play a key role in the aggravation of a broad spectrum of diseases, including mental disorders [ 12 , 13 , 16 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…New data highlight the negative consequences of smoking or nicotine addiction specifically in subjects with mental disorders, beyond the inflammation and oxidative stress which could be a common characteristic for all smokers [ 14 , 15 ]. This relationship is very complex, as smokers can also develop a broad spectrum of non-communicable diseases [ 16 ]. Although this risk is influenced by other individual determinants such as the genome, epigenome, exposome, microbiome, and others, smokers with serious mental illness have an increased risk of dying from cancer, lung disease, and cardiovascular disease, and account for more than 200,000 out of the 520,000 tobacco-related deaths each year [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobacco smoking is one of the major preventable causes of premature deaths globally and is a potentially acquired risk factor for cardiovascular diseases (CVDs), chronic obstructive pulmonary disease, and cancer [ 1 – 3 ]. The scientific literature suggests tobacco smoking to be a causative agent for CVDs and cancers [ 2 ]. According to the World Health Organization, tobacco kills more than 8 million people each year worldwide, including around 1.3 million people who do not smoke but are exposed to second-hand smoke.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is unclear what role nicotine plays, if any, in the carcinogenicity of tobacco smoke. Although some in vitro studies have shown that nicotine may lead to cellular changes associated with cancer initiation and progression ( 20 - 25 ), it is unclear whether these cellular changes are associated with cancer development in vivo in animals, or in humans.…”
Section: Introductionmentioning
confidence: 99%